Pengaruh perilaku sedentary dan status gizi dengan produktivitas melalui tekanan darah ada pekerja di PT. Industri Kapal Indonesia Kota Makassar: The effect of sedentary behavior and nutritional status with productivity for workers at PT. Indonesian Ship Industry Makassar City - Siti Aulia Rahma Ohorella1; Sitti Patimah; Andi Muhammad Multazam (Journal of Muslim Community Health, 2022)
ABSTRACT Introduction: Physical activities that are carried out appropriately and regularly, as well as the frequency and length of time used properly can help increase productivity. The purpose of this study was to analyze the effect of sedentary behavior and nutritional status with productivity for workers at PT. Indonesian Ship Industry Makassar City. Method:  This is a quantitative study using a cross-sectional design. Data analysis using path analysis test (path analysis). The sampling technique in this study was to use the Lemeshow formula (1997) with a sample size of 106 workers. Results: The path analysis test showed that sedentary behavior had no significant effect on blood pressure (p-value = 0.061), the effect of nutritional status on blood pressure was not statistically significant (p-value = 0.278), there was an effect on sedentary behavior. significant effect on productivity (p-value = 0.000), the effect of nutritional status on productivity was not statistically significant (p value = 0.542), the effect of pressure on productivity was not statistically significant (p value = 0.470), sedentary behavior directly affected productivity significantly Regardless of blood pressure (Beta value 0.514., p = 0.000), nutritional status directly affected productivity and not significantly without blood pressure (Beta value 0.052, p = 0.542). Conclusion: of this study suggest that companies hold an exercise program once a week so that workers can stretch their muscles.